2019
DOI: 10.3390/ijerph16162839
|View full text |Cite
|
Sign up to set email alerts
|

Does the Level of Motivation of Physical Education Teachers Matter in Terms of Job Satisfaction and Emotional Exhaustion? A Person-Centered Examination Based on Self-Determination Theory

Abstract: Grounded in self-determination theory (SDT), prior research has demonstrated that physical education (PE) teachers may have different reasons to engage in teaching. Although some person-centered studies have identified varied motivational profiles in PE teachers, none of these studies have included the three forms of motivation (i.e., autonomous motivation, controlled motivation, and amotivation). This study aims to identify teachers’ motivational profiles, using the three forms of motivation. Moreover, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…For example, individuals with emotional exhaustion are prone to chronic diseases [37], reduced job satisfaction, lower job performance [10], diminished organizational loyalty [38], and higher absenteeism [11]. Prior work has primarily focused on the emotional exhaustion of enterprise employees, teachers, and medical staff (e.g., [9,39,40]). Few studies have involved the problem of emotional exhaustion of frontline managers.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…For example, individuals with emotional exhaustion are prone to chronic diseases [37], reduced job satisfaction, lower job performance [10], diminished organizational loyalty [38], and higher absenteeism [11]. Prior work has primarily focused on the emotional exhaustion of enterprise employees, teachers, and medical staff (e.g., [9,39,40]). Few studies have involved the problem of emotional exhaustion of frontline managers.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…Indeed, recent research showed that the perceived transformational relationship between PE teachers’ behavior and students’ PA was stronger when students were harmoniously passionate and self-determined [ 8 ]. Furthermore, Abós et al [ 18 ] showed that autonomously motivated PE teachers, who enjoy and value their teaching, reported lower levels of emotional exhaustion. Thus, autonomous motivation may increase job satisfaction and mental well-being and may also prevent burnout among PE teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, satisfaction of the needs for autonomy, competence and relatedness impacts motivation at work, engagement and satisfaction (Gagné & Deci, 2005). According to Abós et al (2019), experienced PHE teachers are more likely to become actively engaged in their teaching role and to experience greater satisfaction when their motivation is self-determined. There is little research on teachers' motivation during the TI stage, although motivation is frequently mentioned as a contributing factor in their perseverance (Abós et al, 2019;Desmeules, Hamel, & Frenette, 2017).…”
Section: Motivationmentioning
confidence: 99%
“…It appears that type of employment is the main reason for fluctuating motivation levels during the first five years of professional integration. A source of motivation, the contract is considered to offer the stability required to develop relationships with students and evaluate their progress in the opinion of Abós et al (2019). Over the years, contact with the same students and collaboration with colleagues have nuanced the comments of Anna and Victor.…”
Section: Motivationmentioning
confidence: 99%